In silico Study of the Proteins Involved in the Persistence of Brucella spp. - Asadollahi, Parisa; Sadeghifard, Nourkhoda; Kazemian, Hossein; Pakzad, Iraj; Kalani, Behrooz S. (Current Drug Discovery Technologies, 2023)
Background: One of the major problems with Brucella infections is its tendency to become chronic and recurrent, providing a hindrance to the management of this infection. It has been proposed that chronicity is greatly affected by a phenomenon called persistence in bacteria. Several mechanisms are involved in bacterial persistence, including the type II toxin-antitoxin system, the SOS and oxidative and stringent responses. Methods: In this in silico study, these persistence mechanisms in Brucella spp. were investigated. Results: The structure and the interactions between modules involved in these systems were designed, and novel peptides that can interfere with some of these important mechanisms were developed. Conclusion: Since peptide-based therapeutics are a new and evolving field due to their ease of production, we hope that peptides developed in this study, as well as the information about the structure and interactions of modules of persistence mechanisms, can further be used to design drugs against Brucella persister cells in the hope of restraining the chronic nature of Brucellosis.
Keywords: protein interaction